Design of Strategic Planning in Improving Public Sector Organization Performance at TANESCO Morogoro, Tanzania - Uledi , Juma H.; Chachage, Bukaza (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
The study was based on the design of strategic planning for improving public sector organizations. The study employed a case study as the research design to examine design of strategic planning on organizational performance in Tanzania. Strategic management theory was applicable in the study because it showed the rationale that influences the relationship between the theory and the problem under study. The collection of data was done using questionnaires and documentary reviews and based on quantitative data analysis.The inferential analysis was used as a method of data analysis to draw a conclusion. The study findings revealed that the data drawn from the case study of TANESCO Main Office indicated that the design of the strategic planning process was positive and significantly correlated with the dependent variable (performance), thus, design of strategic planning is a major part of the wider activities that influence public institutions' performance. The recommendation is that there should be greater effort on the design of strategic planning for the public sector, but there are some barriers that hinder the implementation of the design of strategic planning, like a lack of information concerning strategic planning. Also, employees must participate in the design of strategic planning and others stakeholders.